DEVELOPING RECOUNT TEXT WRITING ABILITY BY USING STUDENT-GENERATED TEXT OF LANGUAGE EXPERIENCE APPROACH (LEA) - Nanang, Nanang; Supardi, Iwan; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe objective of this reserach is to study how the student-generated text of Language Experience Approach (LEA) develops recount text writing ability of Year 11 students of SMK PGRI Pontianak in academic year of 2015/2016 in terms of vocabulary, sentence fluency, and ideas. This research is a Classroom Action research. The sample is 18 students of Year 11 ofAudio-Visual Technique Class of SMK PGRI Pontianak. The results showed that student-generated text of LEA developed recount text writing ability of the students. Students’ mean score is increased from non-proficient performance level to proficient performance level. It is particularly developed vocabulary, sentence fluency, and conceptual creativity in writing. Besides, it also helped in strengthening speaking, listening, and reading skills, as students had to volunteer information verbally or dictate verbal sentences to the teacher, do some extended writing of the dictated account, listen to teacher reading the text, read and comprehend the text, and write a recount text with their own words. Student-generated text (dictated account) of Language Experience Approach (LEA)is hereby seen as an effective strategy to teach not only recount text writing, but also the other 3 skills of English language. To conclude, student-generated text of Language Experience Approach (LEA) is an alternative strategy that can develop students’ recount text writing ability in many areas, at the same time strengthen speaking, listening, and reading skills. Key Word: Recount Text, Teaching Writing, Student-Generated Text, Language Experience Approach, Classroom Action Research